Al-Quran Buddies E-Hafazan Management - Nurul Athirah, Mohd Marzuki Hussin (2019)
Hafazan is a skill to remember the verses of the al-Quran well although one may not understand it. This is the sign of the greatness of the al-Quran as a miracle that can be memorized compared to Taurat, Injil or any human scripture book that is difficult to memorize. This project will focus on developing website for anyone who wants to memorize the holy verses of the al-Quran. The system help user to memorize al-Quran where they can key in the input or keyword (verses) using Arabic keypad and voice recording. The answers (texts) then will be compared with data in database and immediately get the results. The system also will show the progress of hafazan that had been done by the users. The aim of this project is to help someone learn and memorize the al-Quran in an easy and convenience way. The objectives for this projects are to study and identify the method of learning and memorizing al-Quran, to design and develop a prototype system for al-Quran Buddies E-Hafazan Management using website based that can help to learn and memorize al-Quran and to create test module to test hafazan, the user can key in the input or keyword using Arabic keypad and immediately get the results. They also can test their hafazan by recording an audio. The methodology used in this project is the RAD Methodology which consists of four phases namely analysis, design, develop and testing. After development of the system, client was given the user acceptance test (UAT) to ensure that all function work according to the requirement without any error. The UAT testing ensure the system have achieved the objective. Throughout the project, it can be concluded that memorizing al-Quran needs more discussion and continuous research. ‘Al-Quran Buddies E-Hafazan Management’ can be improved in many different ways by integrating additional features and enhancements to make it more efficient for the users.